Mengukur Kekuatan Tanah Laterit Menggunakan Kaedah Proctor, CBR, Proba Mckintosh Dan Piezocone - Abu Bakar, Azly Zaherman (Universiti Sains Malaysia, 2006)
A laterite soil is examined for its suitability as a construction material by varying the compaction energy and testing its corresponding strenghts in the compacted state using MacKintosh Probe, California Bearing Method (CBR), and Piezocone Methods. Three compaction energy levels are utilised. The results show that the laterite soil constitutes a better material in term of its strength when given an increase amount of compaction energy. The results also show that the maximum strengths as measured using the varying methods gives different optimum moisture contents. By using the standard proctor compaction, its optimum moisture content is the most similar to the one obtain from CBR method. By using the intermediate and modified proctor compactions, their optimum moisture content is very similar to the one obtained from the skin friction of the Piezocone Test. The experiment had suggested that the CBR method at least is showing identical optimum moisture content as the proctor, thus its suitablility for strength measurement as much as proctor can give.